Biobanked tracheal basal cells retain the capacity to differentiate. Issue 6 (20th October 2022) - Kelly, Natalie A.; Shontz, Kimberly M.; Bergman, Maxwell; Manning, Amy M.; Reynolds, Susan D.; Chiang, Tendy
Abstract: Objective: While airway epithelial biorepositories have established roles in the study of bronchial progenitor stem (basal) cells, the utility of a bank of tracheal basal cells from pediatric patients, who have or are suspected of having an airway disease, has not been established. In vitro study of these cells can enhance options for tracheal restoration, graft design, and disease modeling. Development of a functional epithelium in these settings is a key measure. The aim of this study was the creation a tracheal basal cell biorepository and assessment of recovered cells. Methods: Pediatric patients undergoing bronchoscopy were identified and endotracheal brush ( N = 29) biopsies were collected. Cells were cultured using the modified conditional reprogramming culture (mCRC) method. Samples producing colonies by day 14 were passaged and cryopreserved. To explore differentiation potential, cells were thawed and differentiated using the air–liquid interface (ALI) method. Results: No adverse events were associated with biopsy collection. Of 29 brush biopsies, 16 (55%) were successfully cultured to passage 1/cryopreserved. Samples with higher initial cell yields were more likely to achieve this benchmark. Ten unique donors were then thawed for analysis of differentiation. The average age was 2.2 ± 2.2 years with five donors (50%) having laryngotracheal pathology. Nine donors (90%) demonstrated differentiation capacity at 21 days of culture, as indicated by detection of ciliated cells (ACT+) and mucous cells (MUC5B+). Conclusion: Pediatric tracheal basal cells can be successfully collected and cryopreserved. Recovered cells retain the ability to differentiate into epithelial cell types in vitro . Level of Evidence: Level 3. Abstract : While airway epithelial biorepositories have established roles in the study of bronchial progenitor stem (basal) cells, the utility of a bank of tracheal basal cells from pediatric patients, who have or are suspected of having an airway disease, has not been established. In vitro study of these cells can enhance options for tracheal restoration, graft design, and disease modeling. The aim of this study was the creation a tracheal basal cell biorepository and assessment of recovered cells.